Efficacy of group psychoeducation for bipolar I patients : a pilot study - Unnur Samúelsdóttir 1990- (2019)
Background: Barcelona Bipolar Disorder Program is a psychoeducative program for individuals with bipolar I disorder. Hospitals in Denmark have been using the program and included cognitive behavior therapy. The Danish version of the program was translated into Icelandic and is used at Landspítali – The National University Hospital of Iceland. Objective: To examine the efficacy of group psychoeducation for bipolar I patients at Landspítali, and the Bipolar Disorder Attitudes scale (BDAS). This questionnaire seeks to measure attitudes that are considered to influence the treatment and course of the disorder, thereby measuring insight into bipolar disorder. Method: Study 1 had 15 participants that answered the CORE-OM and the DASS, pre and post treatment. The number of times and days of hospitalization, before and after therapy, were also studied. Study 2 had 8 participants that answered questionnaires on five different evaluation time points; the BDAS, the CORE-OM, the DASS, the QOLS, and the DAS. Results: The individuals had been in a stable condition before they started the psychoeducation program, and they remained stable throughout the treatment and at follow-up. Symptoms were relatively stable on average over the measurement points, which confirmed the main hypotheses. The mean number of readmissions to a psychiatric hospital and the number of days of hospitalization decreased after therapy. Conclusion: The results underline the importance of group psychoeducation for bipolar patients. Further studies of psychoeducation and the BDAS over an extended period of time with more participants are required, since the factors influencing the efficacy of treatment in bipolar disorder are not entirely known. Keywords: group psychoeducation, efficacy, bipolar I disorder, Bipolar Disorder Attitudes Scale (BDAS).